The Burden of the "False‐Negatives" in Clinical Development: Analyses of Current and Alternative Scenarios and Corrective Measures. Issue 6 (4th July 2017) - Burt, T; Button, KS; Thom, HHZ; Noveck, RJ; Munafò, MR
Abstract: The "false‐negatives" of clinical development are the effective treatments wrongly determined ineffective. Statistical errors leading to "false‐negatives" are larger than those leading to "false‐positives, " especially in typically underpowered early‐phase trials. In addition, "false‐negatives" are usually eliminated from further testing, thereby limiting the information available on them. We simulated the impact of early‐phase power on economic productivity in three developmental scenarios. Scenario 1, representing the current status quo, assumed 50% statistical power at phase II and 90% at phase III. Scenario 2 assumed increased power (80%), and Scenario 3, increased stringency of alpha (1%) at phase II. Scenario 2 led, on average, to a 60.4% increase in productivity and 52.4% increase in profit. Scenario 3 had no meaningful advantages. Our results suggest that additional costs incurred by increasing the power of phase II studies are offset by the increase in productivity. We discuss the implications of our results and propose corrective measures.